The Architecture of Charisma: Successor to Modernism - Thomas L. Clark (Oz, 1981)
It is no accident that the precepts of Modern Architecture advanced coincidentally with the development of the assembly line. The ideal of the machine was singleminded purpose: the focus of intention…